Prevalence of growth retardation among children and adolescents in China: a systematic review and meta-analysis - Wang, Wei; Qiu, Zhanpeng; Wang, Fang; Qiu, Dongsheng; Ye, Guoping (Frontiers in Pediatrics, 2025)
ObjectiveThe objective of this study was to determine the prevalence of growth delay in Chinese children and adolescents through a meta-analysis, providing scientific evidence for early intervention and prevention.MethodsRelevant studies on the prevalence of growth delay in Chinese children were retrieved from eight major databases: China National Knowledge Infrastructure (CNKI), Wanfang, Chongqing VIP, Chinese Biomedical Literature Database, PubMed, Embase, Cochrane Library, and Web of Science. Two researchers independently assessed the quality of the studies based on the inclusion criteria for cross-sectional studies outlined in the STROBE guidelines. Any discrepancies were resolved through cross-checking. Data extracted from studies were analyzed using Stata 15.ResultsA total of 50 studies were included, with a sample size of 2,644,818 participants. The meta-analysis revealed that the overall prevalence of growth delay in Chinese children and adolescents was 5.7% (95% CI: 5.3%–6.2%). Subgroup analysis by age demonstrated the following prevalence rates: 7.4% (95% CI: 6.6%–8.3%) for ages 0–2 years, 6.8% (95% CI: 6.1%–7.4%) for ages 3–6 years, 3.9% (95% CI: 3.6%–4.2%) for ages 6–12 years, and 3.0% (95% CI: 2.3%–3.6%) for ages 13–18 years. Statistically significant differences were observed between age groups (P < 0.05). With regard to gender, the prevalence was 6.2% (95% CI: 5.4%–7.0%) for males and 6.6% (95% CI: 5.7%–7.5%) for females, with no significant difference between genders (P > 0.05). Analysis by residential area indicated that the prevalence in rural areas was 8.4% (95% CI: 6.2%–10.5%), compared to 3.5% (95% CI: 2.5%–4.4%) in urban areas, showing a statistically significant difference (P < 0.05). Geographically, the Southwest region had the highest prevalence at 9.2% (95% CI: 4.4%–14%), followed by South China (7.0%, 95% CI: 5.7%–8.3%), Northwest China (5.7%, 95% CI: 2.5%–9.0%), Central China (3.8%, 95% CI: 1.4%–6.1%), East China (2.6%, 95% CI: 2.0%–3.2%), and North China (1.8%, 95% CI: 1.1%–2.4%). No significant differences were found in growth delay prevalence among regions (P > 0.05). In terms of study year, the prevalence was 25.8% (95% CI: 2.2%–49.5%) in 2005–2009, 5.2% (95% CI: 3.9%–6.6%) in 2010–2019, and 3.0% (95% CI: 2.7%–3.3%) in 2020–2024, with statistically significant differences observed across years (P < 0.05).ConclusionThe prevalence of growth delay in Chinese children and adolescents is gradually decreasing, with variations across age groups and residential environments. Efforts to alleviate this issue should include enhanced public health awareness, promotion of healthy lifestyles, improved family nutrition education and training, and strengthening of the healthcare system.Systematic Review RegistrationCRD42024579022.